AN ANALYSIS OF SELF-REGULATED LEARNING AMONG HIGH SCHOOL STUDENTS - Andrianie, Santy; Wulandari, Arifah; Krismona, Elwas Berdha; Putri, Dinar Rosani; Aren, Merikan (Jurusan Bimbingan dan Konseling, 2025)
This study aims to analyze the level and characteristics of self-regulated learning (SRL) in senior high school students and its differences based on gender. SRL is understood as students' ability to plan, monitor, and evaluate the learning process independently by involving cognitive, metacognitive, motivational, and behavioral aspects. The study used a descriptive quantitative approach with a sample of 640 senior high school students (312 males, 328 females) selected through a proportionate stratified random sampling technique. Data were collected using an SRL questionnaire adapted from Zimmerman and Pintrich, consisting of four main dimensions: goal setting and planning, self-monitoring, motivational control and learning strategies, and reflection and self-evaluation. The instrument was measured using a four-point Likert scale and had a Cronbach's Alpha reliability of 0.87. Data analysis was conducted descriptively and through an Independent Samples t-test using JASP. The results showed that 82% of students were in the moderate SRL category, 15.3% in the low category, and only 1.8% in the high category, with an average SRL score of 77.19 (SD = 6.22). No students were found in the very high or very low categories. The t-test showed a significant difference between male and female students (t = -2.292; p = 0.022), where female students had a higher level of SRL. These findings emphasize the need for pedagogical strategies and guidance services that explicitly develop SRL through learning models oriented towards autonomy, self-reflection, and responsibility for learning